New insights into human functional ultrasound imaging. (January 2022) - Bertholdt, C.; Dap, M.; Beaumont, M.; Duan, J.; Morel, O.
Abstract: Ultrasound imaging is a vital tool for exploring in vivo the placental function which is essential to understand pathological phenomena such as preeclampsia or intrauterine growth restriction. As technology advances including ready availability of three-dimensional (3D) probes and novel software, new markers of placental function become possible. The objective of this review was to provide an overview of the new ultrasound markers of placental function with a focus on the potential clinical application of three-dimensional power Doppler (3DPD). A broad-free text literature search was undertaken based on human placental studies and sixty full-text studies were included in this review. Three-dimensional power Doppler is a promising technique to predict preeclampsia in the first trimester. However, the influence of external factors such as body mass index, parameter standardisation and machine settings still need to be addressed. Contrast-enhanced ultrasound is currently reserved for research, because the required injected contrast mediums are not currently approved for use in pregnancy, although the safety data is reassuring. Highlights: 3DPD and CEUS are innovative techniques to assess placental function in vivo 3DPD indices are very promising markers for the prediction of preeclampsia. CEUS is promising to understand placental physiology and pathology.